2010
DOI: 10.1007/s00421-010-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of predicting maximal oxygen uptake from a treadmill-based sub-maximal perceptually regulated exercise test

Abstract: The purpose of this study was to determine for the first time whether VO2max could be predicted accurately and reliably from a treadmill-based perceptually regulated exercise test (PRET) incorporating a safer and more practical upper limit of RPE 15 ("Hard") than used in previous investigations. Eighteen volunteers (21.7 +/- 2.8 years) completed three treadmill PRETs (each separated by 48 h) and one maximal graded exercise test. Participants self-regulated their exercise at RPE levels 9, 11, 13 and 15 in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…This is an important application for sedentary individuals and for clinical populations, 12,18 Abbreviations; RPEs, rating of perceived exertions; . VO 2 peak, maximal oxygen uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important application for sedentary individuals and for clinical populations, 12,18 Abbreviations; RPEs, rating of perceived exertions; . VO 2 peak, maximal oxygen uptake.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11,12 The prediction of . VO 2 max from submaximal perceptually guided exercise bouts has been shown to be valid and facilitates a safer and more widely applicable means of exercise testing by eliminating higher exercise intensities (RPE 417) compared with the graded exercise test.…”
Section: Introductionmentioning
confidence: 99%
“…Although perceptually regulated, graded exercise has been used previously in the literature1115 to estimate VO 2max through a submaximal protocol. These protocols have all used extrapolation equations to predict VO 2max based on the submaximal RPE–VO 2 relationship.…”
Section: Introductionmentioning
confidence: 99%
“…These continuous changes in PO during exercise have been shown to be important 16. As these tests do not directly exercise the subject to a maximum, a logical progression of this work would be to create an MIE version of the perceptually regulated exercise test outlined by previous authors 1115. The protocol highlighted in this article, therefore, represents a novel test design for establishing directly measured VO 2max while allowing self-paced, maximal incremental exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in production paradigm studies, research has demonstrated that, when regulating at an RPE 13 (somewhat hard), affective responses are positive in both active and inactive participants (31). An RPE 13 equates to intensities around 50%-70% VOzmax (18)(19)(20)30). Within the recent ACSM Position Stand (3), the use of RPE and affect for exercise prescription is acknowledged, but it is noted that "evidence is insufficient to support these methods as a primary'method of exercise prescription" (p. 1344).…”
mentioning
confidence: 97%